Prerequisites for the Development of Preventive Measures Against Office Syndrome Among Women of Working Age - Olga Lazko; Nataliia Byshevets; Vitalii Kashuba; Yuliia Lazakovych; Igor Grygus; Nataliia Andreieva; Dariusz Skalski (OVS LLC, 2021)
The purpose of the article is to study prerequisites for the development of preventive measures against office syndrome among women of working age.  Material and methods. The research involved 52 female office employees 21 to 57 years old.  Results. The extended clustering of the original data using EM method with the performance of V-fold crosschecking has shown that female office employees are clearly divided into two clusters depending on the manifestation of office syndrome. Despite our assumptions, their division does not depend on age or length of service in the office, but on the manifestation of office syndrome and behavioral characteristics in the work process. Women assigned to different clusters are characterized by statistically significant (p < 0.05) differences between the level of pain in the joints and spine. The research has found that among female office employees with increased musculoskeletal pain, there are statistically significantly (p<0.05) more women with significant overweight and spinal diseases. They are less likely to take active breaks when working at a computer and a larger percentage of them use information technology for entertainment purposes outside the office for 3-4 hours a day. However, a smaller percentage of them work with a PC for more than 7 hours a day. Women with predominant musculoskeletal pain differ in their lifestyle and point to fundamentally different reasons that stop them from taking measures to prevent the risk of occupational diseases. In particular, among female office employees with no office syndrome, a statistically significant (p<0.05) larger share does not need to expand knowledge about the organization of health care in the office and among them the share of those who lead a passive lifestyle predominates.  Conclusions. Thus, these women are potentially at risk of developing office syndrome and, with the absence of preventive measures, are expected to move to the cluster of women with signs of office syndrome. The results of the research indicate the need for different approaches to planning health measures in the work environment, depending on the presence of office syndrome and the level of their responsible attitude to health in the work process.